Pengaruh Pemberian Aromaterapi Lemon Untuk Mengatasi Frekuensi Emesis Gravidarum Untuk Ibu Hamil Trimester Pertama Di PMB Wulan Mardikaningtyas,AMD.KAB Kartasura - Nurhasanah Laila Fitri; Enny Yuliaswati (Pusat Riset dan Inovasi Nasional, 2023)
Background: A pregnant woman in the first trimester is more susceptible to emesis gravidarum, the cause of nausea and vomiting in pregnancy due to an increase in the hormone estrogen and Human Chorionic Gonadrotropin (HCG) poor diet before or in the early weeks of pregnancy, emesis gravidarium in the first trimester pregnant women still occurs and how to deal with it, most people still use pharmacological therapy. Objective: To determine the decrease in the frequency of nausea and vomiting before and after giving lemon aromatherapy to emesis Gravidarum in the first trimester of pregnancy. Method: This type of research with the sampling technique used in this research is probability sampling with simple random sampling method. Results: Before being given lemon aromatherapy to pregnant women in the first trimester who experienced emesis gravidarium on a severe scale, there were 22 people with a percentage of 40.7%, while 32 people with a percentage of 59.3%, after being given lemon aromatherapy for 7 days with the procedure described for pregnant women who experienced emesis gravidaium produced on a mild scale, 33 people with a percentage of 61.1%, while 21 people with a percentage of 38.9%. Conclusion: Lemon aromatherapy is effective for reducing emesis gravidarium in first trimester pregnant women.